Evaluation and management of pest complex in cashew grafts - Deepthy K B (Department of Agricultural Entomology, College of Horticulture, 2003)
Experiments were conducted at Cashew Research Station, Madakkathara and the Departments of Entomology and Pathology, College of Horticulture, Vellanikkara with the objectives of identifying high yielding cashew variety possessing resistance or tolerance to the Tea Mosquito Bug - Colletotrichum gloeosporioides complx and also to develop an effective and safer management strategy using pesticides. Screening of selected cashew grafts against tea mosquito bug (TMB) and Colletotrichum complex revealed that plants infected with TMB alone cause slight damage and may regain their growth after a period of time, but when the plants were . \ inoculated with Colletotrichum and infected by TMB, the plants cannot regain their growth, once the die-back symptoms were incited. The variety 11-1600 was observed to be better as it IS comparatively tolerant to both TMB and TMB-Colletotrichum complex. The varieties Madakkathara- 2, H-1610 and Kanaka also recorded lesser TMB damage. Inoculation with AMF resulted in greater germination percentage and enhanced growth attributes like height, number of leaves, number of roots, fresh weight and dry weight of plants. Among ,the insecticides, quinalphos and carbaryl were effective in reducing the TMB infestation. Combination sprays of carbendaziml copper oxychloride with quinalphos also proved effective against TMB- Colletotrichum pest complex. The scope of rationalising TMB management has been discussed in the light of the relative tolerance of the varieties and the need for judicious application of selected insecticides to contain TMB and of selected fungicides in conjunction to control the subsequent invasion by Colletotrichum gloeosporioides that may aggravate the die- back symptoms highlighted.